THE EFFECT OF PROVIDING HEALTH EDUCATION USING SIMULATION MODEL TOWARD THE IMPLEMENTATION OF HAND WASHING WITH SOAP TO EARLY CHILDHOOD EDUCATION PRESCHOOL AT TUNAS MELATI KINDERGARTEN SANGGAU - Balsia, Yohanes Fredy Oskie (ProNers, 2023)
Background : golden age are the preschool children who are in the age range around 3 "“ 6 years, this phase of age shows curiosity and interest to explore the environment   increases and this is cause of preschool children being suscetible to disease and vulnerable to suffer from hygiene-related diseases, one of them is diarrhea. Diarrhea causes death about 25,2% children under 5 years old in Indonesia. Therefore the most important prevention from this problem is increasing clean and healthy of life behavior, which starts from washing hans.Objective : This reseacrh aims to determine the effect of healthy education by using simulation method toward the implementation of hand washing with soap to early childhood in Tunas Melati kindergarten Sanggau.Method :tthis reseacrh is quantitative model, using one group pretest "“ postest design. The sample in this research by using sampling total, the amount of responden is 26 peoples. Statistic test is using wilcoxon test.Result : hypothesis testing using wilcoxon test result is found signifant result between pre test and post test (P = 0,000), and that showing that is available the effect of healthy education using simulation method toward the implementation hand wash with soap in Tunas Melati kindergarden.Conclusion: model of health  education using simulation method is one of effective way of giving learning topics, because preschoolers children like to learning methods that are motoric and associative.Keyword : simulation, children,hand wash, Healthy education, preschool